PENGARUH KONSENTRASI KALSIUM PROPIONAT DAN DEKSTRIN TERHADAP MUTU FISIKOKIMIA DAN ORGANOLEPTIK MINUMAN SERBUK SARI BUAH PEPAYA - Marlina, Lusi; Kharisma, Ratna Ayu (Jurnal TEDC; Vol 18 No 1 (2024): JURNAL TEDC, 2024)
Papaya fruit (Carica papaya L.) is one of the tropical fruits that can be found everywhere, apart from the delicious taste of this fruit is also rich in complete nutrition with several vitamins contained in papaya fruit. Papaya fruit has a very high tendency to decay, which causes a relatively short shelf life. Therefore, efforts or techniques are needed to process fresh papaya fruit into functional food products with long shelf life. This study was conducted with the aim of determining the effect of the addition of calcium propionate and the amount of dextrin on papaya fruit pollen drinks. This study used an experimental method with a two-factor completely randomized design (RAL), namely the addition of calcium propionate (0.1%, 0.2%, 0.3%) and the addition of dextrin (5 g, 10 g, 15 g) with reference to SNI 01-4320-1996. The test parameters analyzed were water content, vitamin C content, antioxidants, organoleptic tests of color, aroma, taste and texture. The results showed that the addition of calcium propionate and dextrin significantly influenced the water content, vitamin C, antioxidant and organoleptic tests. The addition of calcium propionate concentration (0.1%) and the amount of dextrin (15 g) produced the best quality of papaya fruit pollen drink.